Simultaneous Estimation of the Parameters of the Black-Scholes Option Pricing Models - Rahman, Abdul; Kryzanowski, Lawrence; Sim, Ah Boon (The Review of Economics and Statistics, 1987)
Abdul Rahman, Lawrence Kryzanowski, Ah Boon Sim, Simultaneous Estimation of the Parameters of the Black-Scholes Option Pricing Models, The Review of Economics and Statistics, Vol. 69, No. 4 (Nov., 1987), pp. 727-732